Industrial directory 2010 - Nigeria. Federal Ministry of Commerce and Industry (Abuja: Federal Ministry of Commerece and Industry, 2010)
This is a directory manufacturing establishments in Nigeria with ten employees and above.
oif 03/10/2019
Nigeriana
Keywords: Business enterprises; Industries--Directories; Nigeria